Long-term impact of chronic variable stress in adolescence versus adulthood - Cotella, Evelin Mariel (2019)
Adolescence is a period of active development of stress regulatory neurocircuitry. As a consequence, mechanisms that control the responses to stress are not fully matured during this developmental period, which may result in vulnerability to chronic stress. We hypothesized that adolescent chronic stress would have negative consequences on stress adaptation later in life. Male Wistar rats (PND40) were subjected to chronic variable stress (CVS) for 2 weeks, with 2 daily stressors randomly presented and overnight social stressors twice a week. After five weeks, animals were evaluated during adulthood, using the elevated plus maze (EPM) and the forced swim test (FST). The hypothalamic-pituitary adrenal (HPA) axis response to a 30-min restraint was also assessed. Results are compared to those of adult rats tested 5 weeks following CVS cessation. Our results demonstrate that the long-term effects of CVS are specific to the age of application of the stress regime. We show how behavior and HPA axis response as well as hypothalamic paraventricular nucleus activation can differ with age, resulting in differential behavioral adaptations for animals stressed in adolescence and dysregulation of the HPA axis in the animals stressed in adulthood, These data underscore the importance of the adolescent period in determining resilience of the HPA axis and programming behavioral responses later in life.